Arts and childhood: children's musical styles in a "reflexive" environment - Addessi, Anna Rita; Pscheidt, Jean; Cardoso de Araújo, Rosane (DEDiCA. Revista de Educação e Humanidades (dreh), 2019)
In this article the concept of “musical style” is introduced as a tool to study the relationship between children and art, and the paradigm of “reflexive interaction” as a “device” to enhance the child’s musical style. The concept of musical style will be introduced as a representation of the child’s identity, a way of expressing her/his self with sounds and music, and to be in communication with others. We will introduce the paradigm of “reflexive interaction”, a particular tool that proved able to support and reinforce the individual musical style of each child, in both child-machine and child-adult interaction. Some scenarios of reflexive interaction both in everyday life and music lessons will be introduced and discussed.